Cereal and nonfat milk support muscle recovery following exercise - Liao Yi-Hung; Hara Daiske; Wang Bei; Ding Zhenping; Kammer Lynne; Ivy John L (Taylor & Francis Group, 2009)
Abstract Background This study compared the effects of ingesting cereal and nonfat milk (Cereal) and a carbohydrate-electrolyte sports drink (Drink) immediately following endurance exercise on muscle glycogen synthesis and the phosphorylation state of proteins controlling protein synthesis: Akt, mTOR, rpS6 and eIF4E. Methods Trained cyclists or triathletes (8 male: 28.0 ± 1.6 yrs, 1.8 ± 0.0 m, 75.4 ± 3.2 kg, 61.0 ± 1.6 ml O2•kg-1•min-1; 4 female: 25.3 ± 1.7 yrs, 1.7 ± 0.0 m, 66.9 ± 4.6 kg, 46.4 ± 1.2 mlO2•kg-1•min-1) completed two randomly-ordered trials serving as their own controls. After 2 hours of cycling at 60-65% VO2MAX, a biopsy from the vastus lateralis was obtained (Post0), then subjects consumed either Drink (78.5 g carbohydrate) or Cereal (77 g carbohydrate, 19.5 g protein and 2.7 g fat). Blood was drawn before and at the end of exercise, and at 15, 30 and 60 minutes after treatment. A second biopsy was taken 60 minutes after supplementation (Post60). Differences within and between treatments were tested using repeated measures ANOVA. Results At Post60, blood glucose was similar between treatments (Drink 6.1 ± 0.3, Cereal 5.6 ± 0.2 mmol/L, p < .05), but after Cereal, plasma insulin was significantly higher (Drink 123.1 ± 11.8, Cereal 191.0 ± 12.3 pmol/L, p < .05), and plasma lactate significantly lower (Drink 1.4 ± 0.1, Cereal 1.00 ± 0.1 mmol/L, p < .05). Except for higher phosphorylation of mTOR after Cereal, glycogen and muscle proteins were not statistically different between treatments. Significant Post0 to Post60 changes occurred in glycogen (Drink 52.4 ± 7.0 to 58.6 ± 6.9, Cereal 58.7 ± 9.6 to 66.0 ± 10.0 μmol/g, p < .05) and rpS6 (Drink 17.9 ± 2.5 to 35.2 ± 4.9, Cereal 18.6 ± 2.2 to 35.4 ± 4.4 %Std, p < .05) for each treatment, but only Cereal significantly affected glycogen synthase (Drink 66.6 ± 6.9 to 64.9 ± 6.9, Cereal 61.1 ± 8.0 to 54.2 ± 7.2%Std, p < .05), Akt (Drink 57.9 ± 3.2 to 55.7 ± 3.1, Cereal 53.2 ± 4.1 to 60.5 ± 3.7 %Std, p < .05) and mTOR (Drink 28.7 ± 4.4 to 35.4 ± 4.5, Cereal 23.0 ± 3.1 to 42.2 ± 2.5 %Std, p < .05). eIF4E was unchanged after both treatments. Conclusion These results suggest that Cereal is as good as a commercially-available sports drink in initiating post-exercise muscle recovery.